Modulating arm swing via haptic cueing alters interlimb neural coupling in older adults - Khiyara, Ines; Sidaway, Ben; Hejrati, Babak (Frontiers in Physiology, 2025)
PurposeAge-related gait impairments are strongly associated with increased fall risk, disability, and mortality. While traditional rehabilitation focuses on the lower limbs, arm movements play a key role in stabilizing gait through interlimb neural coupling. This study investigates whether rhythmic haptic cueing of arm swing, which enhances gait, affects interlimb neuromuscular coordination in older adults.MethodsSeventeen older adults (mean age = 73.2 ± 6.0 years) completed three walking conditions: Baseline walking, self-selected Fast walking, and walking while rhythmically receiving haptic cues (Cueing) to increase arm swing frequency and walking speed. Gait speed, arm range of motion (ROM), and intermuscular coherence were analyzed using inertial measurement units (IMUs) and surface Electromyography (sEMG). Coherence and directionality analyses were performed in the alpha (8–15 Hz), beta (15–30 Hz), and gamma (30–60 Hz) frequency bands to quantify neural coupling and intermuscular directionality.ResultsRhythmic Cueing significantly increased arm ROM and gait speed compared to Baseline walking, with improvements comparable to Fast walking. Overall upper–lower limb coherence increased in the alpha and beta bands during Cueing compared to Baseline, with Cueing also exceeding Fast in the alpha band. In specific muscle pairings, significant alpha-band effects were observed in contralateral shoulder–leg pairs, specifically between the left anterior deltoid and right rectus femoris, and between the left posterior deltoid and right biceps femoris. Directionality analysis revealed dominant zero-lag coherence, reflecting shared subcortical and cortical drive in the alpha and beta/gamma bands, respectively, and greater forward-lag coherence during Cueing compared to Baseline, indicating enhanced cortical arm-to-leg influence.SignificanceThese findings demonstrate that externally cued arm swing can modulate gait performance and potentially interlimb neural coupling, activating both subcortical and cortical pathways. Rhythmic haptic cueing shows promise as an intervention for older adults, supporting its potential integration into home-based gait rehabilitation programs.